LEADERSHIP COMPONENTS OF LOCAL GOVERNMENT EXECUTIVES IN SONGKHLA PROVINCE - Maliwan, Ekarach; Thadee, Weerachai; Ramkeaw, Rojjawan (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research on the leadership components of the local administrative organization executives in Songkhla Province had the following objectives: 1) to study the leadership components of the local administrative organization executives in Songkhla Province, and 2) to analyze the survey components of the leadership of the local administrative organization executives in Songkhla Province. A mixed-methods research approach was employed using a focus group discussion with 14 leadership experts for the qualitative research and data collection from 204 local administrative organization executives in Songkhla Province for the quantitative research. The research instrument was a questionnaire with a reliability of 0.91. The statistics used for the data analysis included content analysis, frequency, percentage, mean, standard deviation, and survey component analysis. The research results revealed the following findings. The leadership components of the local administrative organization executives in Songkhla Province consist of five components. The KMO statistical test value was .917, indicating that a total of five leadership components of government executives was sufficient and appropriate to use for the factor analysis statistics due to the KMO value being greater than 0.5. Based on the results of the factor analysis of the survey of the leadership of local government executives in Songkhla Province, it was found that the five components are good management, vision and efficiency, social responsibility, leadership that emphasizes humanity, and success. Regarding the number of components and variance of the leadership component variables of the local government executives, when considering the variance of the variables (eigenvalues) equal to 1, it was found that there were five components and that components 1 to 5 could explain the total cumulative variance equal to 60.427%.